Hypothesis: Cadmium Explains, in Part, Why Smoking Increases the Risk of Cardiovascular Disease. (November 2013) - Hecht, Eric M.; Landy, David C.; Ahn, Soyeon; Hlaing, WayWay M.; Hennekens, Charles H.
Introduction: Cigarette smoking is a major risk factor for cardiovascular disease via acute and chronic mechanisms, some of which remain unclear. One plausible but untested hypothesis concerns cadmium (Cd), a component of cigarette smoke, which is injurious to vascular endothelial cells and is independently associated with cardiovascular disease. To contribute to the formulation of this hypothesis, we performed a meta-analysis of the available data that consisted of cross-sectional studies useful to formulate but not test hypotheses. Methods: PubMed and Google Scholar were searched by combining the terms smoking, Cd, correlation, blood, human, and tobacco. Following abstract review, 10 cross-sectional studies were identified. We compared serum Cd levels between smokers and nonsmokers using standardized mean differences (SMDs) as well as correlation coefficients between smoking and Cd. Results: The estimated overall random effects SMD in Cd between smokers and nonsmokers was 1.13 (95% confidence interval [CI], .70-1.56) with significant heterogeneity (Q = 8.6, P < .001). The estimated overall random effects correlation coefficient between smoking and Cd was .54 (95% CI, .30-.72) with significant heterogeneity (Q = 71.3, P < .01). Conclusions: Despite major inherent limitations of meta-analyses of cross-sectional studies, we believe that the data contribute to the formulation of the hypothesis that Cd explains, in part, why smokers have an increased risk of cardiovascular disease. Further research, including analytic studies designed a priori are necessary to test the hypothesis.